Analysis of Work Performance and Export Competitiveness in Province of Indonesia - Nani Rosita (Faculty of Economics, Universitas Sriwijaya, 2017)
The purpose of this study is to analyse the export performance of provinces in Indonesia, the effect of export and capital stock on the long-term and short-term economic growth of Indonesia and the competitiveness of provinces in exporting Indonesia’s leading products. The panel data from 33 provinces in Indonesia from 2000-2016 is used in this study. The secondary data is consist of gross regional domestic product (GRDP), export value and gross fixed capital formation (GFCF). Export performance is measured using regional export performance index meanwhile, the effect of export and capital stock on long-term and short-term economic growth is analysed using cointegrated panel model and error correction model (ECM) panel. Finally, RCA dynamic is used in analysing export competitiveness. The results show that export performance of each province have various rating on the regional economies. Only 11 provinces have regional export performance index higher than while, meaning that only 33.3% of the total provinces, while the rest of the provinces have index that are less than one. This shows that only few provinces that can provide good performance of export. Based on the co-integrated test, there is a long-term relation between GRDP, export and GFCF. In both long-term and short-term, export and GFCF have positive impact on GRDP showing that the increase in export and/or GFCF will increase GRDP, which will results in economic growth. Furthermore, the results of RCA dynamic show that the export competitiveness is not always following the growth of national export segment. Indonesia’s rubber and coal exports have negative growth of national export segment while export of palm oil, coffee and textile have positive growth.